2018
DOI: 10.26434/chemrxiv.5743638.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bulk Contributions Modulate the Sum-Frequency Generation Spectra of Interfacial Water on Model Sea-Spray Aerosols

Abstract: Vibrational sum-frequency generation (vSFG) spectroscopy is used to determine the molecular structure of water at the interface of palmitic acid monolayers. Both measured and calculated spectra display speci c features due to third-order contributions to the vSFG response which are associated with nite interfacial electric potentials. We demonstrate that theoretical modeling enables to separate the third-order contributions, thus allowing for a systematic analysis of the strictly surface-sensitive, second-ord… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
(108 reference statements)
1
6
0
Order By: Relevance
“…Rather than being due to changes in the H-bonding network, we find that the SFG signal intensity reductions that coincide with raising the salt concentration from 10 µM to 0.1 M are consistent with absorptive-dispersive mixing between χ (2) and χ (3) contributions to the SFG signal generation process from charged interfaces, according to [64][65][66][67][68][69][70]…”
Section: Resultssupporting
confidence: 53%
“…Rather than being due to changes in the H-bonding network, we find that the SFG signal intensity reductions that coincide with raising the salt concentration from 10 µM to 0.1 M are consistent with absorptive-dispersive mixing between χ (2) and χ (3) contributions to the SFG signal generation process from charged interfaces, according to [64][65][66][67][68][69][70]…”
Section: Resultssupporting
confidence: 53%
“…Rather than being due to changes in the H-bonding network, we find that the SFG signal intensity reductions that coincide with raising the salt concentration from 10 μM to 0.1 M are consistent with absorptive–dispersive mixing between χ (2) and χ (3) contributions to the SFG signal generation process from charged interfaces, according to Here, the first two terms are the nonresonant and resonant second-order susceptibility and the third term is given by the inverse Debye screening length, κ, the inverse of the coherence length of the SFG process, Δ k z , and the interfacial potential, Φ(0), multiplied by the third-order susceptibility. ,, We recently showed that, for an exponential distance dependence of Φ­( z ), the χ (3) phase angle, φ, equals arctan­(Δ k z /κ). Using “primitive ion” models, such as Gouy–Chapman theory, we estimate at the low (resp.…”
Section: Resultsmentioning
confidence: 69%
“…spectroscopy provides an indirect measure of ion adsorption, through the changes happening to the interfacial water structure or the surface functional groups. [26][27]33 Recently, Sthoer et al reported an observation of overcharging of Y 3+ and La 3+ ions at arachidic acid (AA) monolayers with SFG spectroscopy. 27 The intensity of -OH region signal (3200 -3700 cm -1 ) decreased as the bulk concentration is increased from 100 nM to 10 M, which is typical due to the decreasing surface charge and disturbed interfacial water organization.…”
mentioning
confidence: 99%